The cutting edge of the poet's sword : Muslim poetic responses to the Crusades - Latiff, Osman. (The Muslim World in the Age of the Crusades, 2017)
In this comprehensive analysis of Arabic poetry during the period of the crusades (sixth/twelfth-seventh/thirteenth centuries), Osman Latiff provides an insightful examination of the poets who inspired Muslims to unite in the jihād against the Franks. The Cutting Edge of the Poet's Sword not only contributes to our understanding of literary history, it also illuminates a broad spectrum of religiosity and the role of political propaganda in the anti-Frankish Muslim struggle. Latiff shows how poets, often used by the ruling elite to promote their rule, emphasised the centrality of Islam's holy sites to inspire the Muslim response to the occupation and later reconquest of Jerusalem, and expressed some surprising views of Frankish Christians.